Molecular cloning and characterization of the 78-kilodalton glucose-regulated protein of Trypanosoma cruzi. - Tibbetts, R S (1994)
The protozoan Trypanosoma cruzi is the etiologic agent of Chagas' disease, an illness responsible for morbidity and death among millions of Latin Americans. Mice also develop this disease when infected with T. cruzi and are a useful model organism for the study of parasite-specific immune responses. To identify immunogenic T. cruzi antigens, serum from an infected mouse was used to isolate clones from a T. cruzi epimastigote cDNA expression library. One of these clones was found to encode the 78-kDa glucose-regulated protein (grp78), the endoplasmic reticular member of the 70-kDa heat shock protein (hsp70) family. Like the mammalian and yeast grp78s, the T. cruzi protein contains an endoplasmic reticular leader peptide and a carboxyl-terminal endoplasmic reticular retention sequence. T. cruzi grp78 is encoded by a tandemly arranged family of three genes located on a chromosome of 1.6 Mb. The effects on grp78 expression of heat shock and tunicamycin treatment, the latter of which specifically stimulates mammalian grp78, were investigated. While the level of the grp78 protein remained constant under all circumstances, grp78 mRNA was unaffected by heat shock but induced fivefold by tunicamycin. Finally, we found that grp78 is the most immunogenic of the T. cruzi heat shock proteins we have characterized, reacting strongly in immunoblots with sera from infected mice.